Development of Pendidikan Pancasila dan Kewarganegaraan Module as Curriculum Combination (K-13 and Merdeka) in islamic primary school - Tuti Marlina; Ziyadatul Khoiriyah (Program Studi Pendidikan Agama Islam (PAI), 2023)
This research aims to produce a product development. The module developed is a combination curriculume module (K-13 and merdeka) because it is an accordance with a orientation of the two curricula and provisions set. The methode applied in this research is research and development (RnD) besed on the Rowntree model. The result of this research are the development of teaching modules. The teaching module developed is in the form of printed modules for pendidikan Pancasila dan kewarganegaraan subjects in class 1 MI. The development process goes through three stages of the Rowntree model, namely: 1) the planning stage (planning) the researhers studies and analyzes starting from the perspective of the basic curriculum and teaching module and analyzing the need of teaching modules from the two curricula provided by kemenag; 2) at the writing preparation stage, the developer combines and develops modules from the two curricula (merdeka and k-13); 3) at the writingband rewriting implementation stage, the developer combines the two modules by implementing, adjusting, compiling and presenting them in a draft from that has been determined by the developer and includes evaluation materialThis research aims to produce a product development. The module developed is a combination curriculume module (K-13 and merdeka) because it is an accordance with a orientation of the two curricula and provisions set. The methode applied in this research is research and development (RnD) besed on the Rowntree model. The result of this research are the development of teaching modules. The teaching module developed is in the form of printed modules for pendidikan Pancasila dan kewarganegaraan subjects in class 1 MI. The development process goes through three stages of the Rowntree model, namely: 1) the planning stage (planning) the researhers studies and analyzes starting from the perspective of the basic curriculum and teaching module and analyzing the need of teaching modules from the two curricula provided by kemenag; 2) at the writing preparation stage, the developer combines and develops modules from the two curricula (merdeka and k-13); 3) at the writingband rewriting implementation stage, the developer combines the two modules by implementing, adjusting, compiling and presenting them in a draft from that has been determined by the developer and includes evaluation material